Fishery women may contribute Significantly in productive activities that lead to family welfare. There are several activities in which the fishery women participate such as sell fish, net repairment and manage small shop. This research is intended to explain women profile in fish processing. The research analysed the role of women in domestic and social aspect, and .their time allocation in various activities. The research result shows thet women keep making a balance contribution between domest - Dina Mardiana; Anna Fatchiya; Yatri Indah Kusumastuti (Buletin Ekonomi Perikanan, 2005)
Fishery women may contribute Significantly in productive activities that lead to family welfare. There are several activities in which the fishery women participate such as sell fish, net repairment and manage small shop. This research is intended to explain women profile in fish processing. The research analysed the role of women in domestic and social aspect, and .their time allocation in various activities. The research result shows thet women keep making a balance contribution between domestic and socual activities. The fIShery women shows that they capable making decition on term .of household cashflow and food preparation. To promote women living quality, the govemment In coordination with various stakeholder could manage related empowerment program.